2009
DOI: 10.1161/circinterventions.108.826172
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Association Between Age and In-Hospital Mortality After Percutaneous Coronary Intervention

Abstract: Background-Temporal trends and contemporary data characterizing the impact of patient age on in-hospital outcomes of percutaneous coronary interventions are lacking. We sought to determine the importance of age by assessing the in-hospital mortality of stratified age groups in the National Cardiovascular Data Registry. Methods and Results-In-hospital mortality after percutaneous coronary intervention on 1 410 069 patients was age stratified into 4 groups-group 1 (age Ͻ40, nϭ25 679), group 2 (40 to 59, nϭ496 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 28 publications
0
55
0
2
Order By: Relevance
“…4,15 In the NCDR registry, 65% of octogenarians were experiencing an acute coronary syndrome (34.89% unstable angina, 18.75% non-STEMI, and 11.35% STEMI). 10 In the current study, only 39.2% of the octogenarians were stable, whereas 10.9% were experiencing a STEMI. This may suggest that although we are taking a larger group of unstable/high-risk octogenarians for cardiac catheterization and intervention, the mortality rates have remained acceptable.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…4,15 In the NCDR registry, 65% of octogenarians were experiencing an acute coronary syndrome (34.89% unstable angina, 18.75% non-STEMI, and 11.35% STEMI). 10 In the current study, only 39.2% of the octogenarians were stable, whereas 10.9% were experiencing a STEMI. This may suggest that although we are taking a larger group of unstable/high-risk octogenarians for cardiac catheterization and intervention, the mortality rates have remained acceptable.…”
Section: Discussionmentioning
confidence: 50%
“…The current study offers a contemporary view of current practice and complication rates with patients having been treated from 2003 to 2008, and to our knowledge, includes the 3rd largest cohort of patients undergoing PCI over 80. 10,11 Poor outcomes among the elderly undergoing PCI were recognized in the early days of angioplasty. Studies prior to the development of intracoronary stenting demonstrated a mortality of approximately 8% to 20%, 11 -14 with many being single-center experiences enrolling less than 60 octogenarians.…”
Section: Discussionmentioning
confidence: 99%
“…760 In 1 series examining trends over a 25-year period, the proportion of patients undergoing PCI who were 75 to 84 years of age doubled, and those Ͼ85 years of age increased 5-fold. 761 Age is one of the strongest predictors of mortality after PCI, 762 and elderly patients present with a substantially higher clinical risk profile 760 Nonetheless, the angiographic success rates and clinical benefits of PCI in elderly patients are similar to younger patients. 763 In fact, the absolute benefit is typically greater because of higher absolute risk of adverse outcomes in these patients.…”
Section: Elderlymentioning
confidence: 99%
“…The most important clinical risk factors associated with in-hospital mortality are reviewed in Table VI [66][67][68][69][70][71].…”
Section: Quantitative Mortality Modelsmentioning
confidence: 99%